First observational record of Siberian weasel Mustela sibirica Pallas, 1773 in Dhorpatan Hunting Reserve, Nepal - Basnet, Hari; Lama, Deepa; Thakur, Manju Shree; Rajbhandari, Prakriti; Bista, Rejina; Vaidya, Rona; Aryal, Prakash Chandra (Nepalese Journal of Zoology, 2022)
Siberian weasel Mustela sibirica Pallas, 1773 is one of the least known small carnivores in Nepal. Only a few authenticated localities of Siberian weasel are known to exist in Nepal. In March 2021, a week-long field trip to the Dhorpatan Valley documented the first confirmed record of Siberian weasel in Dhorpatan Hunting Reserve in Western Nepal.